Analysis and dynamics of multiple-spike waves in neural networks - Davis, Joshua (2018)
Spatially structured bursts of propagating neural activity revealed in cortical slice experiments and in vivo tantalise many scientists on their possible functional mechanisms. Theoretical studies suggest waves with complex firing patterns afford a great capacity for the transmission of information across the brain. This thesis develops a framework for analysing the dynamics of such waves within spiking neuronal networks. We seek to investigate important questions concerning how the wave’s spatiotemporal voltage properties, propagation speed and spike time interval distributions depend on the underlying network structure and the intrinsic features of the neurons that make up the network. These are often difficult to extract with biophysically detailed network models. We therefore analyse simplified spiking networks of synaptically connected neurons, capable of supporting a rich repertoire of propagating activity, yet, amenable to mathematical analysis. Useful information is then obtained on the dynamics of waves found in this network in relation to the model’s parameters. These results can be compared to the findings obtained from more detailed computational studies and experimental observations.